Institutional impacts on diversity, equality and inclusion practices: Case Study of Western multinationals and their emerging economy subsidiaries - Emil Velinov; Andreas Hilger; Pawel Dobrzanski (Zbornik radova Ekonomskog fakulteta u Rijeci : časopis za ekonomsku teoriju i praksu)
This study examines the contextual impacts on the transfer of equality, diversity, and inclusion (EDI) practices from Western multinational corporations (MNCs) to their subsidiaries in emerging economies. The transfer of EDI practices within MNCs has gained significance due to the need to reconcile theory and context while addressing social and managerial tensions associated with EDI. The research aims to answer questions about why and how EDI practices are transferred within MNCs, with a specific focus on the influence of institutional duality on the transfer process. Institutional theory serves as the theoretical foundation, suggesting that the fit between practices and the institutional environment is crucial for their legitimacy and acceptance. The interaction of host and home country factors, shaped by institutional duality, plays a significant role in shaping the transfer and implementation of EDI practices within MNCs. By considering the contextual differences between headquarters and subsidiary institutional environments, this research aims to enhance our understanding of the complexities and challenges associated with transferring EDI practices in suggesting distinct subsidiary identities and agendas. The findings of this study contribute to the literature by shedding light on the contextual factors, and effects of transferring EDI practices within MNCs.